Hubungan antara Pendapatan terhadap Kesejahteraan Subjektif pada Anggota TNI AU di Kota X - Iqhsan Eko Setiawan; M Ridwan Saputra; Arsepta Kurnia Sandra (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aimed to examine the relationship between personeel income beetwean subjective well-being on military personeel. A quantitative survey was performed on a sample of personeels (N = 43) TNI AU in City X and study documents is used to measure how impact of personeel income to personeel’s SWB. The subjective well-being as an independent variable and to measure how subjective well-being correlated each other, this study has used Satisfaction With Life Scale (Diener, 2006) and Positive Affect and Negative Affect Experience (Diener, 2009). Result showed that personeel income is significantly correlate with subjective well-being (p = 0.036, sig. < 0.05). New finding also shows that high and low income are significantly correlate with subjective well-being, limited and recommendation are discussed.